Establishment of BUMDes as a Strengthening of Sustainable Development Goals (SDGs) in Improving Village Economy during the Covid-19 Pandemic - Sipayung, Parlin Dony; Murwadji, Tarsisius; Purba, Hasim; Sukarja, Detania (Talenta Publisher, 2024)
Badan Usaha Milik Desa (BUMDes) as an instrument to drive the village-based economy has shown a significant role in achieving SDGs targets, which amounted to 74 percent before the Covid-19 pandemic hit the world. However, the situation changed during the Covid-19 pandemic, where the focus of the program was on the health and economic recovery process affected by the pandemic. This research was conducted with a descriptive-prescriptive approach that aims to get suggestions on what should be done to overcome the problems faced by BUMDes in the Covid-19 pandemic situation. From the results of this study, it is concluded that in the context of national economic recovery after the Covid-19 pandemic, the participation of all policy makers is needed to formulate the various needs needed to restore the economy at the village level which is also affected by the pandemic. The momentum of the Covid-19 pandemic can be used by the government to ensure the formation of BUMDes in villages while still paying attention to the potential and needs of the village, as well as optimizing the role and operations of BUMDes that have been formed.